Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1097/aog.0b013e31822dac5d
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Complications After Gynecologic Surgery

Abstract: Objective To estimate the association of age, medical comorbidities, functional status, and unintentional weight loss (as a marker of frailty) with postoperative complications in women undergoing major gynecologic surgery. Methods We conducted a cross-sectional analysis of the American College of Surgeons National Surgical Quality Improvement Program 2005-2009 participant use data files were used to analyze gynecologic procedures. The primary outcome was composite 30-day major postoperative complications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
4
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 13 publications
5
47
4
16
Order By: Relevance
“…Most studies were observational (23 of 35) with a total of 1 153 684 patients available for the analysis. Cohorts were composed of patients undergoing lower gastrointestinal (GI) surgery (10 studies), upper GI surgery (6), mixed GI surgery (4), gynaecological surgery (6), urological surgery (4) and mixed abdominal surgery (6) ( Table  1)1 12, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies were observational (23 of 35) with a total of 1 153 684 patients available for the analysis. Cohorts were composed of patients undergoing lower gastrointestinal (GI) surgery (10 studies), upper GI surgery (6), mixed GI surgery (4), gynaecological surgery (6), urological surgery (4) and mixed abdominal surgery (6) ( Table  1)1 12, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of frail patients ranged from 0·5 to 67·2 per cent. Most surgical procedures were performed for cancer; only four studies25 28, 29 41 had fewer than half of the patients without malignancy.…”
Section: Resultsmentioning
confidence: 99%
“…This is somewhat consistent with previous studies which found that only age 80 or older was associated with increased major postoperative complications after gynecologic procedures. 4 Parker and colleagues reported that of 77 patients undergoing benign gynecologic procedures in women age more than 80 years, there was a 14.3% prevalence of postoperative complications, and no mortalities. 5 As displayed in Table 2, there were no patients in this study above the age of 60 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not find an association if women were dichotomized into obese (BMI ≥30 kg/m 2 ) and non-obese women. 4,8 Thus, only extremely low or extremely high BMI appear to be associated with adverse surgical outcomes. This finds further evidence in the present study which, with no obese patients, found no significant association between BMI and postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the literature show that postoperatively complications may occur in a percentage between 12.3% and 20% (1,2,3). Complications require intensive care and close monitoring of patients.…”
Section: Introductionmentioning
confidence: 99%